2019
DOI: 10.3389/fimmu.2019.02327
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Omics Analysis of Autoimmune Skin Blistering Diseases

Abstract: Autoimmune blistering diseases (AIBDs) of the skin are characterized by autoantibodies against different intra-/extracellular structures within the epidermis and at the basement membrane zone (BMZ). Binding of the antibodies to their target antigen leads to inflammation at the respective binding site and degradation of these structures, resulting in the separation of the affected skin layers. Clinically, blistering, erythema and lesions of the skin and/or mucous membranes can be observed. Based on the localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 124 publications
0
19
0
3
Order By: Relevance
“…Bullous pemphigoid (BP) is an autoimmune bullous skin disorder commonly identified in the elderly population. It is an autoantibody-induced cutaneous inflammatory disease against BP180 or BP230 at the dermal-epidermal junctions ( 1 , 2 ). The annual incidence rate of BP has been increasing steadily in the elderly and general populations ( 3 ), and the BP patients were reported to have a significantly increased risk of death compared to the control subjects ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bullous pemphigoid (BP) is an autoimmune bullous skin disorder commonly identified in the elderly population. It is an autoantibody-induced cutaneous inflammatory disease against BP180 or BP230 at the dermal-epidermal junctions ( 1 , 2 ). The annual incidence rate of BP has been increasing steadily in the elderly and general populations ( 3 ), and the BP patients were reported to have a significantly increased risk of death compared to the control subjects ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the patient’s human leukocyte antigen (HLA) typing revealed DQB1*0302, DQA1*0301, and DRB1*04, all of which are associated with pemphigus vulgaris (PV) and DRB1*04, which is also associated with pemphigus foliaceous (PF) (Table 2). 1‐6 DQB1*0302 is most strongly associated with PV, especially a severe form in females 7 . Class II HLA alleles are reportedly most associated with PV and PF, and our patient had three associated class II HLA alleles 2 …”
Section: Figurementioning
confidence: 55%
“…It was postulated that these polymorphisms affect receptor signaling and may be associated with ABDs susceptibility. Recent investigative efforts included the identification of mutations in genes encoding immunological molecules and their possible associations with pathological autoimmune response in various dermatoses [10,25]. Previous reports indicated that CD32B polymorphisms may be associated with systemic lupus erythematosus [26].…”
Section: Discussionmentioning
confidence: 99%